Where is "Out There"? - Graboi, Dan (Journal of Scientific Exploration, 2024)
Experimental evidence and verified individual accounts show that visual and other types of information from distant minds and environments can enter the conscious as well as the unconscious mind of an individual and can measurably affect brain and body function. The information appears to pass through every physical obstacle and does not degrade in quality with increasing distance in the path between source and receiver. No signal can be detected with current physical instrumentation. What is the medium in which this “psi-encoded information” appears to propagate? What is its format? What is its lifetime? Selected examples of apparent psi information propagation from differing types of sources are presented and analyzed. In order to account for the behavior observed in the examples, a worldview developed in the Advaitic thought tradition is considered, in which a non-physical domain interacts with the physical domain of matter-energy and spacetime. A main currency of the non-physical domain is postulated to be psi-encoded information. It is concluded that this information does not propagate through space. Other characteristics of the non-physical domain and its content are inferred from the examples. They provide a framework in which the nature of psi-encoded information and its processing may be further explored.